Socialization of the Use of YouTube Videos as a Learning Media for Class XII Students of Private Madrasah Aliyah Al Washliyah 30 Binjai - Irhamuddin, Irhamuddin (Jurnal Kegiatan Pengabdian Mahasiswa (JKPM), 2023)
This service article describes the socialization of the use of YouTube videos as a learning medium for class XII students at the private Madrasah Aliyah Al Washliyah 30 Binjai. The aim of this community service is to provide education and advocacy to the public that digital technology has a strategic role as a learning medium. This type of article writing is qualitative service which seeks to explain and describe the sincere and sincere service of madrasa teachers to society, especially to students in transferring knowledge to the nation's children, which has been carried out and then described in a structured manner by following the applicable rules of writing scientific papers. The results of writing this article show Firstly, YouTube videos are the right media to be used as a source of teaching material so that students can learn at school and at home thereby stimulating students' intelligence. secondly, YouTube shows are easily accessible to students andoften watched together using a projector device. third, YouTube shows are packaged in interesting language that is easy for students to understand and are held for 30 minutes.